2016
DOI: 10.21614/chirurgia.111.6.487
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Pathological Profile and Surgical Outcome of Patients of Gastrointestinal Tuberculosis Undergoing Laparotomy

Abstract: Inspite of specific antituberculous drugs and vast measures against the disease, including chemoprophylaxis and pasteurisation abdominal tuberculosis remains a fairly common disease even today. Gastrointestinal tuberculosis has an indolent course and the common mode of presentation is usually sub acute or chronic. Prompt surgical exploration, vigilant postoperative care and administration of ATD helped to treat the patients successfully with their complete cure and rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…nutritional status, with concurrent signs of pulmonary TB as well as a high rate of intra/preoperative positivity of tissue samples for tuberculosis/acid-fast bacilli (AFB). [12][13][14][15][16][17][18] As with those studies, intestinal obstruction due to varied mani-festations of abdominal Koch's was the commonest etiology for surgical intervention, followed closely by bowel perforation, intra-peritoneal abscess, etc. [9][10][11] Stoma formation was required in most cases, as was the wound complication rate, despite adequate care, whereas, death rate was low.…”
Section: Resultsmentioning
confidence: 99%
“…nutritional status, with concurrent signs of pulmonary TB as well as a high rate of intra/preoperative positivity of tissue samples for tuberculosis/acid-fast bacilli (AFB). [12][13][14][15][16][17][18] As with those studies, intestinal obstruction due to varied mani-festations of abdominal Koch's was the commonest etiology for surgical intervention, followed closely by bowel perforation, intra-peritoneal abscess, etc. [9][10][11] Stoma formation was required in most cases, as was the wound complication rate, despite adequate care, whereas, death rate was low.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 61.2% subjects presented with obstruction and 29% with peritonitis. 13 On the study of Afridi et al, only 16% subjects treated with anastomosis and found 12.5% subjects with anastomosis leaks. 14 On study of Islam et all, out of 37 subjects with peritonitis and ten subjects with frozen abdomen, three subjects treated with anastomosis and all were found leaks.…”
Section: Discussionmentioning
confidence: 96%
“…Anastomosis leaks found in a subject who underwent bypass anastomosis for a severe adhesion, as resection is not possible to proceed. Pathak et al 13 reported one enterocutaneous fistula out of 49.9% resection and anastomosis. Charokar et al 16 found no anastomotic leakage in primary perforation repair.…”
Section: Discussionmentioning
confidence: 98%
“…Saat ini diagnostik berdasarkan gejala klinis, endoskopi, radiologi dan patologis akan menjadi kunci untuk mendiagnosis TB usus. 1,2,4,8 Umumnya tatalaksana TB usus dengan pemberian OAT dan pembedahan untuk memperbaiki komplikasi yang akan menghasilkan resolusi secara signifikan terhadap gejala gastrointerstinal. Adanya komplikasi berupa perforasi usus, perdarahan gastrointestinal, obstruksi total pada pasien akan memberikan prognosis yang buruk.…”
Section: Kesimpulanunclassified